Outcomes and costs of remote patient monitoring among patients with implanted cardiac defibrillators: An economic model based on the PREDICT RM database. (29th April 2019) - Hummel, James P.; Leipold, Robert J.; Amorosi, Stacey L.; Bao, Haikun; Deger, Kristen A.; Jones, Paul W.; Kansal, Anuraag R.; Ott, Lesli S.; Stern, Sean; Stein, Kenneth; Curtis, Jeptha P.; Akar, Joseph G.
Abstract: Background: Remote monitoring of implantable cardioverter‐defibrillators has been associated with reduced rates of all‐cause rehospitalizations and mortality among device recipients, but long‐term economic benefits have not been studied. Methods and Results: An economic model was developed using the PREDICT RM database comparing outcomes with and without remote monitoring. The database included patients ages 65 to 89 who received a Boston Scientific device from 2006 to 2010. Parametric survival equations were derived for rehospitalization and mortality to predict outcomes over a maximum time horizon of 25 years. The analysis assessed rehospitalization, mortality, and the cost‐effectiveness (expressed as the incremental cost per quality‐adjusted life year) of remote monitoring versus no remote monitoring. Remote monitoring was associated with reduced mortality; average life expectancy and average quality‐adjusted life years increased by 0.77 years and 0.64, respectively (6.85 life years and 5.65 quality‐adjusted life years). When expressed per patient‐year, remote monitoring patients had fewer subsequent rehospitalizations (by 0.08 per patient‐year) and lower hospitalization costs (by 554 per patient year). With longer life expectancies, remote monitoring patients experienced an average of 0.64 additional subsequent rehospitalizations with increased average lifetime hospitalization costs of 2784. Total costs of outpatient and physician claims were higher with remote monitoring (47 515 vs 42 792), but average per patient‐year costs were lower (6232 vs 6244). The base‐case incremental cost‐effectiveness ratio was 10 752 per quality‐adjusted life year, making remote monitoring high‐value care. Conclusion: Remote monitoring is a cost‐effective approach for the lifetime management of patients with implantable cardioverter‐defibrillators.